PENINGKATAN MINAT BELAJAR SISWA DALAM PEMBELAJARAN KIMIA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD - Bekti Mulatsih (Ideguru: Jurnal Karya Ilmiah Guru, 2017)
Research conducted in chemistry learning through cooperative learning model of Student Teams Achievement Divisions (STAD) type in Class X.1 SMA N 1 Banguntapan Bantul aims to increase students' interest in learning chemistry which is limited to learning Reaction Reduction Oxidation. Interests observed include three aspects of pleasure and interest, attention, and want to learn and in addition to aspects of communication. The type of research conducted is Classroom Action Research (PTK). The study was conducted in two cycles. Cycle I consists of three meetings, and cycle II of four meetings, at each end of the cycle held a quiz. The data obtained from the results of observations conducted on the activities of teachers and students when the action is implemented. From the research results can be concluded that is (1) STAD type cooperative learning process that can increase student learning interest are as follows: (a) students in small group of four or five members, based on final repeat semester 1. Each group consists of team with different cognitive abilities namely, high, medium, and low. Students study in groups after being given materials, students mutual cooperation in understanding the material or completing the tasks that exist in the Student Work Sheet (LKS). LKS contains questions that will be done afterwards will be a summary of material that is easily understood by the students. After group learning is done quiz. The results of the quiz in the scores to determine individual improvement points and subsequently used to determine the points of the group, the group that gets the points above the criteria that have been awarded, (b) during the group activities, the teacher goes from one group to another to provide guidance to students or groups experiencing difficulties. (2) With STAD type cooperative learning, students' interest in learning chemistry has increased. In the first cycle, the average of students' learning interest is 56,53% with medium criterion, and the second cycle of learning interest is 80,39% with very high criterion. Student communication also increases. In cycle I mean of student communication in learning chemistry 46,57% with medium criterion, cycle II mean of student communication increased to 63,73% with high criterion.